Study some specifications of copolymer (PLA-PEG): دراسة بعض الخصائص لمزائج البوليميرات المشتركة من بولي لاكتيك أسيد وبولي إتيلين غليكول (PLA-PEG) - Gema Farzat Khlil, Husine Ahmed Baker, Ghazal Mohamad Tohmaz (Journal of engineering sciences and information technology, 2022)
This study about the blends of Poly Lactic Acid/ Poly Ethylene Glycol (PLA/PEG) 4000 copolymer at concentrations (9%,6%,3%,0%)) wt%) from (PEG) and (PLA) (5%) (w/w) by using casting solvent method to production films. The nonwoven nano fibrous mats were obtained by electro spinning of (PLA/PEG) solutions in chloroform, at weight ratios (70/30) (v/v), respectively. DSC is employed to measure the crystallinity difference between (PLA/PEG) blends and their nonwovens mats. the thermal properties (DSC) of (PLA/PEG) copolymer blends films and electrospun nano fiber mats such as (Tm) melting temperature, (Tg) glass transition temperature, (Tc) crystallization, Xc crystallinity rate and enthalpy . the FTIR test was done for all samples to figure the nature linking between (PLA) and (PEG),the results were that (6%) (w/w) of (PEG) was the optimized rate to apply Electrospinning method , data of DSC test defined that (Tg) and (Tm) were decreased, and that refer to occurrence physicist cross linking between the used substances (Completely miscible blend) when the electrospinning method was applied, also Xc for these nonwoven mats was decreased which has in turn an important effect on the speed of biodegradble for poly lactic acid (PLA).